CONVERSION IN INDIA TODAY - Vempeny, Ishanand (Journal of Dharma, 2003)
A little more than a decade ago I was attending a seminar on Christian Fundamentalism held in Manila, Philippines. I had the opportunity of meeting various groups of fundamentalists including those with military names like the Navigators of the Lord, Crusaders for World Conquest, etc. For the seminar, we had invited the representatives from some five groups for a panel discussion. All of them propounded the ideal that only those who have been baptized through the Holy Spirit and have had the experience of having been born again could attain eternal salvation. According to them, not only the Non-Christians but also the Christians of the Main Line Churches (who constitute more than 90% of Christians) will go to eternal hell. Since the seminar was organized by the Catholics, they made an effort to find some loopholes for the salvation of some of the Catholics under certain conditions.